A non-klatskin tumor: A case report and review of intrabiliary hydatid cyst rupture. (2020) - Alimoradi, Mersad; El-Helou, Etienne; Sabra, Hassan; Hani, Pierre; Wakim, Raja
Highlights: There's no consensus on definitions & types of intrabiliary hydatid rupture. Original classification included either frank or occult rupture. Hydatid cyst rupture should always be ruled out as a cause of biliary obstruction. MRI may miss the diagnosis, and ERCP is valuable in diagnosis and treatment. Surgical removal of the mother cyst is essential for treatment. Abstract: Introduction: A 64-year-old lady was diagnosed with having a klatskin type 3A tumor based on imaging, however, an alternative diagnosis was achieved during surgery. Presentation of case: We present a case of a 64-year-old lady who presented for new-onset jaundice and was diagnosed with type 3A klatskin tumor based on MRCP findings. During surgery, it was revealed that the obstruction was caused by a frank intrabiliary hydatid cyst perforation. Choledocoscopy with irrigation, cholangiography, and removal of the mother cyst were performed, and an end-to-end biliary anastomosis over a t-tube was then done. The patient tolerated the intervention and recovered well. Discussion: Hydatid cyst disease of the liver usually follows a benign course, however, intrabiliary rupture is one of the common complications associated with this disease. Intrabiliary rupture is classified into either frank or occult. Frank perforation, which is more common, is when hydatid material passes into the biliary ducts, and it may cause biliary obstruction and cholangitis with a high mortality rate. Occult perforation is when the hydatid cyst becomes infected itself, which usually leads to a silent presentation, and may only cause signs of suppuration. Diagnosis is usually achieved by imaging and relevant history. Treatment consists of medical and surgical intervention. Intraoperative cholangiography, choledocoscopy, and t-tube drainage are recommended during surgery for frank rupture. Conclusion: Intrabiliary hydatid cyst perforation can mimic cholangiocarcinoma and must be considered as an alternative diagnosis in these patients prior to surgery.